Degenerate sweeping process with a Lipschitz perturbation. Issue 14 (26th October 2021) - Kecies, Mohamed; Haddad, Tahar; Sene, Moustapha
Abstract : In this paper, we prove a theorem concerning the existence and uniqueness of a solution for a degenerate sweeping process with a Lipschitz single valued perturbation in Hilbert space. An application to differential complementarity problems is given.